2019
DOI: 10.1016/j.adaj.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and rehabilitation of musculoskeletal disorders in oral health care professionals

Abstract: Background:The objective of this systematic review was to describe the evidence for preventive and rehabilitative interventions for musculoskeletal disorders in dental professionals.Types of Studies Reviewed: Systematic search, screening, and eligibility processes were conducted to identify experimental, quasi-experimental, observational, and survey research studies that either directly evaluated or predicted the effects of preventive or rehabilitative interventions on the reduction of musculoskeletal symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 35 publications
2
31
1
3
Order By: Relevance
“…In regards to the duration of pain and discomfort episodes related to different anatomical regions, it was found that most symptoms were suffered by individuals for seven or fewer days. This may have been related to uncomfortable working postures and long working hours [5,9,22]; indeed, 50% of orthodontists work even on Sundays [24]. Moreover, the longest episodes were reported for the neck and lower back zones, similar to the findings of a study by Newell and Kumar, which investigated orthodontists in Alberta [14].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In regards to the duration of pain and discomfort episodes related to different anatomical regions, it was found that most symptoms were suffered by individuals for seven or fewer days. This may have been related to uncomfortable working postures and long working hours [5,9,22]; indeed, 50% of orthodontists work even on Sundays [24]. Moreover, the longest episodes were reported for the neck and lower back zones, similar to the findings of a study by Newell and Kumar, which investigated orthodontists in Alberta [14].…”
Section: Discussionsupporting
confidence: 76%
“…These differences may be explained by the fact that in comparison to older orthodontists, recently graduated orthodontists work more often, tend to have more workplaces, have more frequent patient care appointments (of 20 minutes or less) and work for longer periods (more than 8 hours a day). These factors might lead to early-onset MSDs [28] and greater MSD symptoms in both young orthodontists [14,24] and young DDSs than in older professionals [5,9,22,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long term MSDs could affect one’s quality of life. Therefore, identifying factors associated with musculoskeletal problems in the dental workplace is of high importance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying factors associated with musculoskeletal problems in the dental workplace is of high importance. 8 Various studies have been done to record self-perceived health and health-related behaviors of dental students in other countries, 9,10 but little is known about the health of dental students in the United Arab Emirates (UAE). Currently only one study investigated the occupational health problems among dentists in the UAE; conducted by Al-Ali and Hashim, 11 which demonstrated that musculoskeletal disorders were the most common (68%) occupational health problem.…”
Section: Introductionmentioning
confidence: 99%